2010
DOI: 10.1007/s00216-010-4153-2
|View full text |Cite
|
Sign up to set email alerts
|

An efficient approach for the isolation, identification and evaluation of antimicrobial plant components on an analytical scale, demonstrated by the example of Radix imperatoriae

Abstract: Using Radix imperatoriae (the root of masterwort) as an example, we describe an efficient approach for the isolation, identification and evaluation of bioactive plant components on an analytical scale. The extraction of Radix imperatoriae with ethyl acetate was enhanced by the application of ultrasound oscillations. This rhizome extract was applied to three pathogenic bacteria (Bacillus cereus, Escherichia coli, and Staphylococcus aureus) to determine its antimicrobial activity. Disk diffusion was utilized to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Beside environmental factors, viral infections and life-style are responsible factors for its increasing frequency (Alavian et al 2011;Gurevich-Panigrahi et al 2009). Natural products are a frequent inspiration for the development of new anti-cancer drugs (Ghavami et al 2010;Gokay et al 2010;Panigrahi et al 2012). As outlined above, much attention in recent years has been paid to experimental drugs that modulate autophagy or apoptosis.…”
Section: Closing Remarksmentioning
confidence: 99%
“…Beside environmental factors, viral infections and life-style are responsible factors for its increasing frequency (Alavian et al 2011;Gurevich-Panigrahi et al 2009). Natural products are a frequent inspiration for the development of new anti-cancer drugs (Ghavami et al 2010;Gokay et al 2010;Panigrahi et al 2012). As outlined above, much attention in recent years has been paid to experimental drugs that modulate autophagy or apoptosis.…”
Section: Closing Remarksmentioning
confidence: 99%
“…The structures of these compounds were elucidated by spectroscopic methods ( 1 H-NMR, 13 CNMR, DEPT, HMBC, HSQC, COSY) and HR-MS as well as by comparison of their NMR data with those reported in the literature. [14][15][16][17][18][19][20] Compound ( 14 In addition, a survey of the literature showed that this compound has been isolated from the shoots 4 and the roots 15 of Pituranthos triradiatus. However, this is the first time that this compound was isolated from P. Chloranthus.…”
Section: Resultsmentioning
confidence: 99%
“…The fractions were further isolated by PTLC to obtain pure compounds. Five furanocoumarins were elucidated and identified by LC-MS and 1 H NMR as follows: bergamottin (C21H22O4, MW 338), 6',7'-dihydroxybergamottin (C21H24O6, MW 372), 6',7'-epoxybergamottin (C21H22O5, MW 354) oxypeucedanin (C16H14O5, MW 286), oxypeucedanin hydrate (C16H16O6, MW 304) [10][11][12][13][14].…”
Section: Isolation Of Active Compounds From Flavedo By Chromatographimentioning
confidence: 99%